2007
DOI: 10.1038/sj.bjc.6603609
|View full text |Cite
|
Sign up to set email alerts
|

Sustained elevation of Epstein–Barr virus antibody levels preceding clinical onset of nasopharyngeal carcinoma

Abstract: We have monitored Epstein -Barr virus (EBV) IgA antibody levels of 39 nasopharyngeal carcinoma (NPC) cases for up to 15 years before clinical onset of NPC, and assessed preclinical serologic status of another 68 cases. Our results identify a serologic window preceding diagnosis when antibody levels are raised and sustained. This window can persist for as long as 10 years, with a mean duration estimated to as 37728 months. Ninety-seven of these 107 NPC cases exhibited such a window. Cases that did not may refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
138
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 24 publications
9
138
0
3
Order By: Relevance
“…early recognition of NPC (17)(18)(19). However, the presence of these antibodies among moderate numbers of non-NPC individuals has caused difficulties in the use of EBV specific IgA antibodies to differentiate populations at high risk for NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…early recognition of NPC (17)(18)(19). However, the presence of these antibodies among moderate numbers of non-NPC individuals has caused difficulties in the use of EBV specific IgA antibodies to differentiate populations at high risk for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Elevated levels of antibodies against latent and lytic EBV proteins have been found among the sera of NPC patients. 16,17 While numerous studies have compared the different profiles of EBV antibodies between NPC and non-NPC individuals, a specific serological test which can be reliably used for NPC screening is still unavailable. It seems likely that the carrier state and periodic activation of EBV in asymptomatic infections within the general population have produced significant background levels of EBV antibodies among some non-NPC individuals, who may remain free of disease or experience onset of malignancy several years later.…”
mentioning
confidence: 99%
“…Similarly, the presence of serum immunoglobulin (Ig)A antibodies against the EBV capsid antigen (VCA-IgA) has also been identified to be associated with an increased risk of NPC (24,25). It has been demonstrated that NPC patients with higher levels of VCA-IgA have poorer prognoses (26,27). Given that plasma EBV-DNA is superior to VCA-IgA in sensitivity, specificity and predicting the prognosis of patients with NPC (28), plasma EBV-DNA may replace the conventional VCA-IgA antibody test in the diagnosis and management of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal cancer patients often shows increase in antibody response of IgA and IgG against VCA, EA, EBNA1 and transcription activator Zta and Rta, as well as other EBV lytic cycle protein (Henle and Henle, 1976;Fachiroh et al, 2004). Elevation of antibody responses to EBV may precede onset of clinical manifestation of NPC by 1 to 5 year (Yip et al, 1994;Ji MF et al, 2007). Combined EBV serological biomarkers could improve diagnostic value of NPC (Neel and Taylor, 1990;Fachiroh et al, 2006;Liu et al, 2012;Ai et al, 2013;Chang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%